2000
DOI: 10.1073/pnas.97.7.3319
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive diversification within a large family of recently duplicated, placentally expressed genes

Abstract: The pregnancy-associated glycoproteins (PAG) are putative peptide-binding proteins and products of a large family of genes whose expression is localized to the placental surface epithelium of artiodactyl species. We have tested the hypothesis that natural selection has favored diversification of these genes by examining patterns of nucleotide substitution in a sample of 28 closely related bovine, caprine, and ovine family members that are expressed only in trophoblast binucleate cells. Three observations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(34 citation statements)
references
References 27 publications
1
31
0
2
Order By: Relevance
“…A high degree of similarity is also observed in the UTR sequences, suggesting that these regions may also be functional. This analysis argues in favor of a high positive selection (39,43) and suggests that this retrogene encodes a functional protein.…”
Section: Snail-like Is An Encoding Gene Subjected Tomentioning
confidence: 99%
See 1 more Smart Citation
“…A high degree of similarity is also observed in the UTR sequences, suggesting that these regions may also be functional. This analysis argues in favor of a high positive selection (39,43) and suggests that this retrogene encodes a functional protein.…”
Section: Snail-like Is An Encoding Gene Subjected Tomentioning
confidence: 99%
“…1B. The nature of nucleotide substitutions in terms of the ratios of transitions (t)/transvections (T) and of synonymous (S, non-aa-changing)/non-synonymous (NS, aa-changing) variations can be used as an indicator of the degree of positive selection within the amino acid sequence (39). We found no difference between the intermediate and C-terminal regions with respect to t/T, but the percentage of NS changes was higher in the intermediate region.…”
Section: Analysis and Expression Of An Intronless Snail-like Retrotramentioning
confidence: 99%
“…Phylogenetic studies have shown that PAGs segregate into one ancient group and a more recent group , Hughes et al 2000. The latter refers to modern molecules that appeared about 52 millions years ago, whereas the ancient group includes members that have probably existed for about 87 millions years.…”
Section: Introductionmentioning
confidence: 99%
“…It is perhaps not surprising that gene duplication has long been suggested to provide the raw materials on which adaptive evolution can act (6). Indeed, expansion of gene families is often a species-specific phenomenon, with certain gene families restricted to closely related species or single phylogenetic orders (7)(8)(9). Speciation itself could even be a natural outcome of gene duplications (3,10).…”
Section: Gene Familiesmentioning
confidence: 99%